Mimikrija kao simbolička slika svijeta - Medarić, Magdalena (1996)
The article discursses the possibility of adapting the concept of
mimicry, a generally accepted term in the natural
sciences as a concept in the history of contemporary
culture as well.
Projekt MZOS
ENG